Is the Car Dependency of Urban and Rural Residents a Measurable Phenomenon? Development of an Indicator-based Measurement Approach for the Stuttgart Region, Germany - Siedentop, Stefan; Roos, Sebastian; Fina, Stefan (Raumforschung und Raumordnung | Spatial Research and Planning, 2013)
There is much agreement among spatial and transport planners that urban and rural areas have increasingly become dependent on motorized transport over time, and have therefore also become more energy intensive. This paper understands “automobile dependence” as a form of structural dependence on the availability of the private motor car which results from a lack of alternative mobility options. It introduces a methodological approach for a location sensitive assessment of settlement structures with regards to their degree of automobile dependence. The methodology is based on an indicator concept that analyses the availability and quality of public transport and the accessibility of critical facilities with non-motorized transport options. The study approach is implemented in the Stuttgart region and allows for an absolute or relative assessment of car dependency in various spatial units. The results provide evidence for the existence of urban areas with a significant structural automobile dependence in Stuttgart, even in a region where public transport is generally highly developed.
Keywords: Car dependency; Urban spatial structure; Transportation; Mobility; Spatial planning